Analysis of the Principal's Role in Building Institutional Image and Work Professionalism in the Junior High School Education Environment: Analisa Peran Kepala Sekolah Dalam Membangun Citra Lembaga Dan Profesionalisme Kerja Di Lingkungan Pendidikan Sekolah Menengah Pertama - Alamsyah Rizky Ramadhan; Nurdiansyah Nurdiansyah (Academia Open, 2022)
This study wants to reveal the answer to the problem of the principal in building the image and professionalism of the work in the educational institution he leads. What did the principal do to maintain the school's image and expertise? This is what encourages researchers to analyze the role of school principals in building the image of the institution and work professionalism in the Al-Irsyad Kraksaan Middle School Education environment. This research is a type of qualitative research. Data collection techniques using interviews and questionnaires that researchers can through telephone and documentation. Which researchers use data analysis techniques Triangulation, namely different data collection techniques to obtain data from the same source. Based on the results of the study indicate that the principal in building the image of educational institutions by planning, curriculum development, manpower management, student services, development of learning facilities and resources, innovative learning, teacher motivation, and the presence of internal factors. The impact of this research is expected to be a motivation for the principal for the development of the school he leads.